Pengembangan Tes Bahasa Arab Berbasis QuickAppNinja untuk Meningkatkan Keterampilan Menulis Siswa Kelas VIII di MTs. Hikmatul Amanah - Muhammad Lutfi Asfihani; Annisa Septifara; Muqimah Liwais Sunnah (Institut Kariman Wirayudha Sumenep Madura, 2026)
The utilization of technology in education today focuses on improving the quality of learning, especially as a more effective learning medium. At MTs. Hikmatul Amanah, the Arabic learning evaluation process still uses conventional methods in the form of paper tests. The purpose of this research is to develop an evaluation test using QuickAppNinja learning media for Arabic lessons that is valid, reliable, feasible, and practical to use. In addition, this study aims to help students facilitate Arabic language learning, especially in improving their writing skills. The development of this test model used the ADDIE approach. Data collection techniques included interviews, observations, questionnaires, and tests. The data were analyzed using qualitative and quantitative methods. The study was conducted on VIII grade students at MTs. Hikmatul Amanah Mojokerto by using relevant research samples. The validation results show that this learning media is feasible to use. Validation questionnaires submitted to media, material, and language validators showed positive results: validation by media experts obtained a percentage of 82% with a very valid level of validity, validation by language experts reached 81% with a very valid level of validity, and validation by material experts got 58% with a sufficient level of validity. In addition, the N-gain Score test results calculated from the pretest and posttest scores reached 61, which is categorized as moderately effective. Thus, QuickAppNinja app is proven to be effective to be used as Arabic learning media, helping students improve their writing skills significantly.